2011
DOI: 10.1016/j.bbalip.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Lipid particles/droplets of the yeast Saccharomyces cerevisiae revisited: Lipidome meets Proteome

Abstract: In the yeast Saccharomyces cerevisiae as in other eukaryotes non-polar lipids are a reservoir of energy and building blocks for membrane lipid synthesis. The yeast non-polar lipids, triacylglycerols (TG) and steryl esters (SE) are stored in so-called lipid particles/droplets (LP) as biologically inert form of fatty acids and sterols. To understand LP structure and function in more detail we investigated the molecular equipment of this compartment making use of mass spectrometric analysis of lipids (TG, SE, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
226
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(247 citation statements)
references
References 64 publications
18
226
1
2
Order By: Relevance
“…Induced by Oleic Acid-It is well known that oleate preferentially induces TAG synthesis and its accumulation in LPs in yeast (5,14). Because radiolabeling studies have indicated that Gat1p and Gat2p differentially contribute to TAG synthesis (8), we decided to study their role in response to oleate.…”
Section: Cells Lacking Gat1p Do Not Accumulate Lipid Particlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Induced by Oleic Acid-It is well known that oleate preferentially induces TAG synthesis and its accumulation in LPs in yeast (5,14). Because radiolabeling studies have indicated that Gat1p and Gat2p differentially contribute to TAG synthesis (8), we decided to study their role in response to oleate.…”
Section: Cells Lacking Gat1p Do Not Accumulate Lipid Particlesmentioning
confidence: 99%
“…It is well known that synthesis of lipids is spatially restricted by the localization of biosynthetic systems. Intriguingly, evidence points to Gat1p (but not Gat2p) as an LP resident protein, although this has only been detected during stationary phase in cells cultured in the presence of glucose (5,10,11). In addition, localization studies in actively growing cells showed that both Gat1p and Gat2p are localized to the ER, possibly enriched in distinct ER regions (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Each type of organisms contains a specific set of them, for example, perilipins in mammal cytosolic OBs (Kimmel et al, 2010), 19 proteins in fungi (Grillitsch et al, 2011), and phasins in bacterial OBs (Yang et al, 2012). The most abundant plant proteins associated with OBs are oleosins (Capuano et al, 2007;Huang et al, 2009).…”
mentioning
confidence: 99%